Peran ECPAT Indonesia dalam Menangani Kejahatan Pariwisata Seksual Terhadap Anak di DKI Jakarta - Calista Happy Andiani; Ika Riswanti Putranti (Journal of International Relations Diponegoro, 2019)
Indonesia is one of the third largest child sexual tourism destinations in the world. As the capital of Indonesia, DKI Jakarta is the second highest tourist entrance after Bali. In addition, DKI Jakarta is also the main location that has the highest threat of child sexual exploitation in Indonesia. Nevertheless, the Indonesian government has not provided clear protection for children. This study aims to describe the role of ECPAT Indonesia to assist the Indonesian government in dealing with child sexual tourism in DKI Jakarta, using theories of liberal institutionalism, international organizations, and international cooperation. In this study, the role of ECPAT Indonesia was limited from 2012 to 2018. Child sex tourism has rapid development so it needs cooperation from various parties, one of which is ECPAT Indonesia. From 2015 to 2017 cases of commercial sexual exploitation of children were not as high as in previous years. This is inseparable from the collaboration between the Indonesian government and ECPAT Indonesia. The role of ECPAT Indonesia is divided into three sectors, the government, private and community sectors.